Cellular biomarkers of exposure to the fungicide copper oxychloride, in the common garden snail Helix aspersa, in Western Cape vineyards - Snyman, Reinette Georgenie (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD(Agric)(Botany and Zoology))--University of Stellenbosch, 2001.